O Pronatec como fomentador da inclusão social no Ceará: uma análise dos resultados obtidos pelo IFCE - Vieira, Armenia Chaves Fernandes (2015)
This paper analyzes the process of implantation and development of the technical courses offered in the Federal Institute of Education, Science and Technology of Ceará (IFCE), more specifically on the campuses of Fortaleza, Maracanaú and Morada Nova through the National Program of Access to Technical Education and Employment (PRONATEC), the subprogram of which is the Student Education Scholarship. The goal of this work is to identity the results obtained through the PRONATEC on the cited campuses, as to the indicators of access, permanence and success of the educational process of the students, analyzing the factors which emerged which in some way could have influenced the results obtained. It is a case study which was orientated by a bibliographical and documental analysis which gave the basis for the theoretical referential regarding the theme facilitating the comprehension of relevant aspects about the PRONATEC as a social inclusion program. We sought to answer in this study the following question: how did the process of technical professional education at the high school level take place in the ambiance of the PRONATEC in the courses offered by the IFCE? The analysis of this issue is the essence of the general goal of this investigation, the specific goals of which are: explain the trajectory of technical professional education at the high school level in Brazil relating it to productive and social development; contextualize the PRONATEC as a social inclusion program investigating the process of implantation of the technical courses at the high school level offered by this Program on three campuses of the IFCE; present the results of the indicators of access, permanence and success as to the educational process of the students benefitted by the PRONATEC at the IFCE analyzing the possible factors which contributed to the results obtained. Initially, there is a brief exposition about the history of professional education in Brazil relating it to productive and social development. There follows an approach to the program with a focus on the national implantation and in the IFCE contextualizing it as a program of social inclusion of the Dilma Housseff government. Finally, an analysis is made of the development of the PRONATEC technical courses on the campuses researched presenting their results and making an analysis of this data. In this way one intends to contribute, with this study, to a better comprehension and reflection about the PRONATEC as a social inclusion program of professional education through the analysis of its implantation and development process and of the results obtained in the educational process of its students relating to access, permanence and success.